PERBEDAAN CELAH MIKRO PASAK GLASS PREFABRICATED FIBER REINFORCED DAN PASAK PITA POLYETHYLENE FIBER REINFORCED DENGAN MENGGUNAKAN SISTEM ADHESIF TOTAL- ETCH (PENELITIAN IN VITRO) - Yuli Fatzia Ossa; Wandania Farahanny; Bakri Soeyono (Journal of Syiah Kuala Dentistry Society, 2016)
Fiber reinforced composite post often used to increase the retention of the crown restoration after endodontic treatment. Retention of fiber reinforced composite post it was obtained through a system adhesif of cement luting resin. The problem of luting cement based resin is often occurs polymerization shrinkage thus a microleakage. This study attempts to look at the differences micro gap of glass prefabricated fiber reinforced post and ribbon polyethylene fiber reinforced post by using ahesif system total etch. Root canal treatment on 20 of the premolars first mandible have extracted for the orthodontic treatment. Coronal part of the teeth were banished, then used glass prefabricated fiber reinforced post and ribbon polyethylene fiber reinforced post. To evaluate the micro gap on both the post adhesif technique was used penetration dyestuff methylene blue 2 %. The entire sample diveded into three parts horizontally namely coronal, middle, and apical. The upper part of peces of these sample observed under stereomicroscop with enlargement 20 x, were a score 0-4 in the area expansion of penetration dyestuff. The result of statistical test Kruskal Wallis Test show there are significant differences (p 0,05) in group glass prefabricated fiber reinforced post and ribbon polyethylene fiber reinforced post. However the result of statical test Mann- Whitney test show significant differences on the coronal and middle (p0,083) while on the apical there is no significant difference (p 0,083).Keywords: glass prefabricated fiber reinforced post, polyethylen fiber reinforced, micro gap